Melhoria do simulador do sistema turbogerador - Fratini, Marcelo Henrique Canciano (2023)
The turbogenerator system, comprising a crucial turbine and generator component in power generation systems, along with an initial boiler, has seen advancements in technology over the years, leading to new possibilities in system control. However, before implementing these controls in the final system, validation becomes necessary. To achieve this, a turbogenerator system simulator was developed using a Programmable Logic Controller (PLC) and a Human-Machine Interface (HMI). Nevertheless, the current simulator faces challenges in accurately reproducing real system behaviors and maintaining computational efficiency for simulations. Such limitations may result in imprecise and inadequate outcomes, hindering the analysis of various turbogenerator operational scenarios, and prolonging Factory Acceptance Testing (FAT) for electrical panels storing the system's control, encompassing PLC, HMI, Speed Regulator, Protection Relays, and other components based on complexity. This work aims to enhance the simulator, addressing these limitations, to reduce engineering time for validating new controls and improve FAT efficiency. Assessing the necessary improvements for the simulator, some limitations in analog inputs and outputs hindered the implementation of all enhancements. Therefore, focus was placed on impactful improvements, including two controls: Digital Synchronizer and Load Control (DSLC) by Woodward for load control and Woodward's 505 model for power control. The simulator's PLC is WEG PLC 300, and the WEG HMI was utilized, with improvements made in ladder language to match the existing code. Testing DSLC control necessitated revising the previous code due to deviations from expectations. Power control with the speed regulator showed oscillation of 1.24% above and 0.72% below the desired value, with an error of approximately 0.98% during testing. Moreover, load control with DSLC revealed that higher simulated loads increased oscillation rate and control error. In conclusion, the implemented simulator improvements signify significant strides in understanding and optimizing the turbogenerator system, resulting in more efficient FAT work and reduced engineering time investment in this process.